2006
DOI: 10.1038/nn1813
|View full text |Cite
|
Sign up to set email alerts
|

A new naturally occurring GABAA receptor subunit partnership with high sensitivity to ethanol

Abstract: According to the rules of GABA(A) receptor (GABA(A)R) subunit assembly, alpha4 and alpha6 subunits are considered to be the natural partners of delta subunits. These GABA(A)Rs are a preferred target of low, sobriety-impairing concentrations of ethanol. Here we demonstrate a new naturally occurring GABA(A)R subunit partnership: delta subunits of hippocampal interneurons are coexpressed and colocalized with alpha1 subunits, but not with alpha4, alpha6 or any other alpha subunits. Ethanol potentiates the tonic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
263
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(279 citation statements)
references
References 51 publications
13
263
3
Order By: Relevance
“…However, as reported above, EtOH had no significant effect on GABA A -mediated IPSC amplitude or frequency. GABA also activates extrasynaptic receptors following spillover of GABA from release sites (Glykys et al, 2007;Wei et al, 2004) or accumulation of GABA in the extracellular space. To test whether GABA A signaling is involved in EtOH's effect on spike firing, recordings were performed in the presence of the GABA A receptor antagonist picrotoxin (100 mM).…”
Section: Effects Of Etoh On Ofc Neuron Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, as reported above, EtOH had no significant effect on GABA A -mediated IPSC amplitude or frequency. GABA also activates extrasynaptic receptors following spillover of GABA from release sites (Glykys et al, 2007;Wei et al, 2004) or accumulation of GABA in the extracellular space. To test whether GABA A signaling is involved in EtOH's effect on spike firing, recordings were performed in the presence of the GABA A receptor antagonist picrotoxin (100 mM).…”
Section: Effects Of Etoh On Ofc Neuron Excitabilitymentioning
confidence: 99%
“…N ¼ 5-7 for each treatment group. current that can influence neuronal excitability (Glykys et al, 2007;Wei et al, 2004). To directly examine the role of extrasynaptic GABA A receptors in EtOH action, we monitored holding current before and during local application of EtOH and GABA A receptor blockers.…”
Section: Effects Of Etoh On Extrasynaptic Gaba and Glycine Receptor Fmentioning
confidence: 99%
“…In addition, it is currently a subject of debate as to whether low concentrations of alcohol affect only α 4 , α 6 and δ subunits (Lovinger and Homanics, 2007), For example, it has been shown that co-application of low concentrations of ethanol (17mM) influences channel potentiation of at least the α 1 β 2 γ 2 receptor by neurosteroids (Akk et al, 2007). Moreover, α 1 δ subunit assemblies that are highly sensitive to low concentrations of ethanol and mediate tonic inhibitory currents have recently been detected in hippocampal interneurons (Glykys et al, 2007). Taken together, the importance of tonic inhibition for vulnerability to alcoholism has yet to be clearly elucidated.…”
Section: Presynaptic Postsynaptic and Extrasynaptic Receptors: Phasimentioning
confidence: 99%
“…Other experiments done with the recombinant expression systems have shown that 3-30 mM alcohol is enough to activate  and subunit containing receptors (Wallner et al, 2003;Sundstrom-Poromaa et al, 2002). This effect is shown to increase the tonic inhibition (Wei et al, 2003;Hanchar et al, 2005;Glykys et al, 2007;Santhakumar et al, 2007;Liang et al, 2008), the specific form of inhibition mediated by the -GABAARs.…”
Section: Alcohol and Extra-synaptic Gabaarsmentioning
confidence: 92%
“…This is especially important as the extra-synaptic GABAARs are thought to be most sensitive to ethanol at levels of social drinking, i.e., less than 30 mM (Sundstrom-Poromaa et al, 2002;Wallner et al, 2003Wallner et al, , 2006Wei et al, 2003;Hanchar et al, 2005;Santhakumar et. al., 2007;Glykys et al, 2007;Olsen et al, 2007). Studies of δ subunit knock out mice have shown the impact of extra-synaptic δ -GABAARs for mediating the effects of ethanol (Mihalek et al, 2001).…”
Section: Alcohol and Extra-synaptic Gabaarsmentioning
confidence: 99%